Precise Orbit Determination of CubeSats Using Proposed Observations Weighting Model - Allahvirdizadeh, Amir; El-Mowafy, Ahmed; Wang, Kan (Springer, 2022)
CubeSats can be used for many space missions and Earth science applications if their orbits can be determined precisely. The Precise Orbit Determination (POD) methods are well developed for large LEO satellites during the last two decades. However, CubeSats are built from Commercial Off-The-Shelf (COTS) components and have their own characteristics, which need more investigations. In this paper, precise orbits of 17 3U-CubeSats in the Spire Global constellation are determined using both the reduced-dynamic and the kinematic POD methods. The limitations in using elevation-dependent weighting models for CubeSats POD are also discussed and, as an alternative approach, a weighting model based on the Signal-to-Noise Ratio (SNR) has been proposed. One-month processing of these CubeSats revealed that around 40% of orbits can be determined at the decimeter accuracy, while 50% have accuracy at centimeters. Such precise orbits fulfil most mission requirements that require such POD accuracy. Internal validation methods confirmed the POD procedure and approved the distinction of weighting based on SNR values over the elevation angles.